BURUNG GAGAK SEBAGAI IDE DALAM KARYA SENI GRAFIS - Syauqi, Dr. Budiwirman, M.Pd., Yofita Sandra, S.Pd., M.Pd. (Serupa The Journal of Art Education, 2018)
The purpose of this final work is to visualize and reveal the crow as ideas in graphic artwork with hopes can change the view of society about some assumption than the crow’s myth as messenger death animal. The embodiment of concept, the author displayed the phenomena and unique fact about social life of the crow itself as the main subject matter.This final artwork used several stages: The first is preparation, looking for the art ideas based on the references about the crow in internet. The second is elaboration. The author analyzed the data. The third is synthesis. The author arranged the implementation schedule. The fourth is sketch design. The last is the implementation the ideas to be a graphic artwork. The author displayed the phenomena and unique fact about crow social life itself.This ten graphic artwork visualized about the phenomena and unique fact about the crow social life. The artwork collected all behavior and characteristic of the crow itself. As for the ten artworks are: 1) habit 2) love to shower 3) faithful 4) community 5) survive 6) lurking 7) law 8) intelligence 9) execution 10) responsibility.Keyword: Bird, Raven, Idea, Art Graphic